Tools for collaborative software inspection management / Lai Poh Fatt - Lai , Poh Fatt (2005)
Inspection Manager is web based system that is used by the Inspection moderator, Inspector and Document Author. Inspection Moderator can manage his inspection process properly here. Inspection can set the inspection objective, invite the inspections, review the defects discovery logs, schedule for the inspection overview or inspection meeting and etc. Meanwhile, the inspector can retrieve the to be inspected document here have their preparation for meeting by finding potential defects in the document and log the defects through inspection manager. The author can upload their document here and correct explain the defects. The system is also available online 24 hours a day throughout the year. The aim of this project is to build a software inspection tool to replace the existing manual process in order to upgrade the business strategies. The core objective of this system is to build a web based application which allowing all tasks to be done through electronic. Researches are done on the existing system to get a better view of traditional software inspection process. The Rational Unified Process is used to develop the inspection manager. Inspection manager is an active web page solution that needs special development tools and languages such as ASP.NET, Internet Information Server (IIS), Macromedia Dreamweaver MX and others.